Etiological factors of severe acute malnutrition and impact of nutrition rehabilitation centre: a prospective observational study from Bhavnagar - Gamit, Vibhuti D.; Gohil, Jayendra R.; B., Adithya Nikhileshwar; Vagh, Tanmay P. (International Journal of Contemporary Pediatrics, 2021)
Background: Severe acute malnutrition (SAM) causes almost half of childhood deaths in children <5 years in developing countries. In India, as National Family Health Survey (NFHS), prevalence of SAM has increased from 6.4 in NFHS-3 (2005-2006) to 7.5% in NFHS-4 (2015-1016); [5.8 to 9.5% Gujarat]. The aim of study was to determine the etiological factors and outcome of SAM and the benefit of nutrition rehabilitation centre (NRC) among 6 months to 5 years children at the Pediatrics, NRC ward, Sir T. General Hospital. Methods: A prospective observational study of 151 SAM children over nine months. Etiological factors were determined by history and relevant investigations, exclude other systemic disorders. Therapeutic nutrition was provided for 14 days. Cases were followed up two weekly for 2 months by monitoring weight after NRC admission. Results: Association was found between Small for gestational age (64.9%), joint family (59.6%) and low birth spacing (59.6%) as etiological factors leading to SAM. 81.5% children gained weight during 14 days NRC stay. Weight gain was noted at follow-up. Defaulter rate increased from 9.9% at discharge to 28.5% at 2 months follow-up. Weight was static for 9% children. 34.4% children were from rural area and 65.6% from urban area. 23.8% children had received pre lacteal feed. Timing of complementary feeding was incorrect in 29%. There were no deaths. Conclusions: Small for gestational age, joint family, low birth spacing, and incorrect feeding practices and urban residence were etiological factors. NRC stay (defaulter rate 26%), produced weight gain in SAM children.